2012
DOI: 10.1123/ijsnem.22.6.486
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Single Dose of Green Tea Polyphenols on the Blood Markers of Exercise-Induced Oxidative Stress in Soccer Players

Abstract: Acute ingestion of GTP (640 mg) does not attenuate exercise-induced oxidative stress and muscle damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 44 publications
1
67
0
Order By: Relevance
“…The results from recent studies have shown that green tea catechins can affect levels of ROS [79][80][81][82], increase levels of antioxidants [83][84][85][86], decrease levels of inflammatory substances [87,88], and increase TAC (TAS) [84,86,87]. An excellent summary of earlier studies that measured ROS and TAC can be found in a chapter by Serafini et al 2011 [67].…”
Section: Oxidative Stressmentioning
confidence: 97%
“…The results from recent studies have shown that green tea catechins can affect levels of ROS [79][80][81][82], increase levels of antioxidants [83][84][85][86], decrease levels of inflammatory substances [87,88], and increase TAC (TAS) [84,86,87]. An excellent summary of earlier studies that measured ROS and TAC can be found in a chapter by Serafini et al 2011 [67].…”
Section: Oxidative Stressmentioning
confidence: 97%
“…Some human studies have shown positive effects for endurance including V02 max [145], fat oxidation, and insulin sensitivity [146] in an untrained population; however, studies on trained subjects are yet to show benefits [147149]. It is unlikely that supplemental catechins would be beneficial to ultra-endurance performance.…”
Section: Reviewmentioning
confidence: 99%
“…They concluded that dietary supplementation with GTE may provide protection against oxidative damage induced by both short-term muscular endurance test and long-term strength training. In another Jówko et al's study [19], green tea catechins-treated soccer players were able to perform a higher number of lift repetitions during the muscle endurance test, but none of the analyzed plasma biomarkers was affected by the ingestion of green tea catechins, suggesting that a 640 mg dose was too low to attenuate exercise-induced oxidative stress and muscle damage. Hodgson et al [24] found that in healthy physically active men, GTE enhanced lipolysis and fat oxidation when compared to placebo, but only under resting conditions, whereas no effect of GTE was seen during exercise.…”
Section: Introductionmentioning
confidence: 99%